Sport and PE: A Complete Guide to Advanced Level Study - Wesson, Kevin [et al] (London Hodder and Stoughton, 2002)
This text has been fully revised to give full coverage of the new AS and A level specifications. The expert author team have built on the success of the best-selling first edition; each chapter includes activities, revision questions and a range of activities for AS and A2. Each section contains new material and the comparative elements of sport have been extended to make the book suitable for all A level specifications.
Includes Illustrations and Index
Keywords: Physical education and training